Persistence in world export patterns and productive capabilities across two globalizations - Isabella Weber; Gregor Semieniuk; Junshang Liang; Tom Westland (University of Massachusetts, Department of Economics, 2022)
We construct a new global commodity-level export dataset to analyze the persistence of export patterns as proxies of productive capabilities across the first and the current waves of globalization. We find that productive capabilities are path-dependent and historical capabilities are powerful predictors of countries' incomes today. This is robust to controlling for persistence in geography, institutions, and colonial status, and confirmed by instrumenting past capabilities with asymmetric reductions in travel times following the switch from sailing to steamboats. We also show that the "great specialization" in primary goods and manufacturing goods exporters coincided with a great polarization in global diversification levels.
Keywords: O33; O47; F02; F14; F6; 330; persistence; globalization; productive capabilities; development; global export patterns